Experimental investigations on the fibre length degradation in injection moulds - Moritzer, Elmar; Martin, Yannick (AIP conference proceedings, 2017)
The sustainable use of natural resources such as raw materials and fuels, and the carbon footprint of products are becoming increasingly important in many industrial sectors. Due to the substitution of materials such as steel and aluminium, the use of fibre-reinforced thermoplastic materials has increased dramatically in recent years. The properties of injection moulding products are considerably dependent on the resulting fibre length in the components. Increased fibre length results in a significant improvement concerning tensile strength, stiffness and impact strength of the moulded parts. The fibre length reduction occurring in the injection unit is already the subject of current research, while the decrease inside of injection moulds has hardly been investigated. By the use of a special design and arrangement of the cavities, a modification of the runner system, as well as a gate adjustment a reduction in the shortening of the reinforcing fibres in the injection mould can be achieved. Thus, the material potential can be utilized better by these optimizations. In the presented study different injection moulds were examined by determining the length of fibre at different locations along the flow path. From these results, the most important factors influencing the fibre damage can already be identified.